My name is barbra eaudiobook - Streisand, Barbra (Books on Tape, 2023)
The long-awaited memoir by the superstar of stage, screen, recordings, and television PLEASE NOTE The audiobook edition is read by Barbra Streisand. Features additional anecdotes and music that are exclusive to the My Name is Barbra audiobook. Barbra Streisand is by any account a living legend, a woman who in a career spanning six decades has excelled in every area of entertainment. She is among the handful of EGOT winners (Emmy, Grammy, Oscar, and Tony) and has one of the greatest and most recognizable voices in the history of popular music. She has been nominated for a Grammy 46 times, and with Yentl she became the first woman to write, produce, direct, and star in a major motion picture. In My Name Is Barbra , she tells her own story about her life and extraordinary career, from growing up in Brooklyn to her first star-making appearances in New York nightclubs to her breakout performance in Funny Girl on stage and winning the Oscar for that performance on film. Then came a long string of successes in every medium in the years that followed. The book is, like Barbra herself, frank, funny, opinionated, and charming. She recounts her early struggles to become an actress, eventually turning to singing to earn a living; the recording of some of her acclaimed albums; the years of effort involved in making Yentl ; her direction of The Prince of Tides ; her friendships with figures ranging from Marlon Brando to Madeleine Albright; her political advocacy; and the fulfillment she’s found in her marriage to James Brolin.   No entertainer’s memoir has been more anticipated than Barbra Streisand’s, and this engrossing and delightful book will be eagerly welcomed by her millions of fans.